El Método Viso-Audio-Motor-Gnósico en el aprendizaje de la ortografía del quinto grado de EGB de la Unidad Educativa “8 de Diciembre - Luna Córdova, Cinthya Rosemary (2023)
The following research called the visual-audio-motor-gnosic method has as its general objective: To analyze the incidence of the visual-audio-motor-gnostic method in learning orthography in the fifth grade of Basic General Education of the Educational Unit "8 de Diciembre ", To comply with this objective, three specific objectives were developed, the first focused on identifying the orthography level in which the fifth grade of BGE is, the second on proposing multisensory spaces through the visual-audio- motor-gnostic method for the improvement of orthography, and the third objective was aimed at evaluating the use of the visual-audio-motor-gnostic method in orthography. To carry out this study, a descriptive type of research was used, with a quantitative-qualitative approach and non-experimental design, during the process the analytical, inductive, deductive and statistical methods were applied, the techniques used were observation, interview, pre-evaluation and post-evaluation, these contributed significantly to the data collection. The research population was the educational unit "8 de Diciembre " from which 16 students and 1 teacher were selected through a non-probability sampling. It is important to mention that the results of the research indicate that the main purposes of the visual-audio-motor-gnostic method contribute in a significant way to the learning of orthography, the same that allowed to strengthen their abilities and skills, in addition, it should be emphasized that students learn in different ways. Keywords: learning, orthography, method, students, macro skills.